Marketing management practices in an emergency care department - Pop-Micle, Ligia Sanda Marinela (J Med Life, 2021)
The aim of this case study was to identify effective marketing management strategies in the Emergency Care Department of a Romanian Emergency Hospital. An observational design study was conducted, and the instrument for collecting the data was the self-administered questionnaire. Out of 100 questionnaires completed, 74 proved to be valid. The statistical analysis was performed using the IBM SPSS Statistics software version 20 and Microsoft Office Excel 2013. Quantitative variables were described by means and standard deviations, whereas for the qualitative variables, frequencies and percentages were used. Most of the respondents were aged between 28 and 35 years (33.8%) and women (60.8%). The emergency room (ER) physicians identified the following factors as being important in becoming very good doctors: continuous specialization (81.1%), reading medical literature (78.4%), and getting involved in more complicated cases (78.4%). The ER physicians mentioned that most of their patients were satisfied with the medical information received (31.1%), properly understood the medical information received (18.9%), and 68.9% of the doctors considered that patients were showing them total respect. Although 40.5% of the ER physicians declared they were suffering from burnout, 25.7% felt satisfied and joyful in their daily activities. Today’s context triggered the need to integrate the concept of consumer value-driven care in the health care system, especially in the ER departments, by implementing the principles of efficient marketing management practices.